Kadar Kreatinin dalam Sampel Darah 15 Menit dan 30 Menit Sebelum Disentrifugasi - Arum Puspita, Fenita; Haiti, Margareta; Felicia Lubis, Agnes (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
A clinical laboratory is a facility that performs examinations of clinical samples related to health conditions, including three stages: pre-analytical, analytical, and post-analytical. Creatinine is a crucial indicator in assessing kidney function and is frequently used in clinical chemistry assessments. Creatinine test results are significantly influenced by the preanalytical phase, particularly the length of time the blood is allowed to stand before centrifugation. This standing allows the blood to fully clot before centrifugation. The aim of this study was to determine creatinine levels in blood samples 15 minutes and 30 minutes before centrifugation. This study used a quantitative approach characterized by a cross-sectional analytical observational design with a sample size of 38 people.Using an SST-type test tube containing a clot activator can enhance the clotting process. Creatinine examination was performed using the Bio System BA 200 instrument, with analysis using the Wilcoxon test. The average creatinine level in blood samples centrifuged 15 minutes after sampling was 0.78 mg/dL, while in samples centrifuged 30 minutes after sampling, the level was 0.79 mg/dL. The Wilcoxon Signed Rank test produced a p-value of 0.706 (p>0.05). The results showed no difference in creatinine levels in blood samples left for 15 minutes and 30 minutes before centrifugation. Further research can be recommended using the Jaffe method using alternative tubes (Plain, Clot)